2019
DOI: 10.1016/j.brainresbull.2019.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of liraglutide on the development of epilepsy and behavioural alterations in two animal models of epileptogenesis

Abstract: Liraglutide (LIR) is a novel long-lasting glucagon-like peptide-1 (GLP-1) analogue that facilitates insulin signalling and shows also neuroprotective properties in different brain disease models. In this study, we explored the potential antiepileptogenic effects of LIR in two different animal models; namely, the mouse intrahippocampal kainic acid (KA) model of temporal lobe epilepsy and the WAG/Rij rat model of absence epileptogenesis. Moreover, we evaluated LIR effects on comorbidities in various behavioural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 70 publications
3
19
0
Order By: Relevance
“…In addition, during this study we narrowed our focus on the influence of ketone supplement-evoked effects to the adenosinergic system. Nevertheless, this WAG/Rij rat strain is extensively used for investigation of different drugs on CNS diseases [1,[67][68][69][70][71], and the present study further supports our previous experiments [23] on the role of the adenosinergic system. It has been suggested that the ketosis/βHB-evoked increase in adenosine levels [14] can modulate influence of ketone supplements not only on different CNS diseases [8,32,36], but also sleep and sleep-like effects [20,21,[28][29][30] via adenosinergic system (likely through A1Rs).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, during this study we narrowed our focus on the influence of ketone supplement-evoked effects to the adenosinergic system. Nevertheless, this WAG/Rij rat strain is extensively used for investigation of different drugs on CNS diseases [1,[67][68][69][70][71], and the present study further supports our previous experiments [23] on the role of the adenosinergic system. It has been suggested that the ketosis/βHB-evoked increase in adenosine levels [14] can modulate influence of ketone supplements not only on different CNS diseases [8,32,36], but also sleep and sleep-like effects [20,21,[28][29][30] via adenosinergic system (likely through A1Rs).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, during this study we narrowed our focus on the influence of ketone supplement-evoked effects to the adenosinergic system. Nevertheless, this WAG/Rij rat strain is extensively used for investigation of different drugs on 13 CNS diseases [1,[67][68][69][70][71], and the present study further supports our previous experiments [23] on the role of the adenosinergic system. It has been suggested that the ketosis/βHB-evoked increase in adenosine levels [14] can modulate influence of ketone supplements not only on different CNS diseases [8,32,36], but also sleep and sleep-like effects [20,21,[28][29][30] via adenosinergic system (likely through A1Rs).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, the main goal of the present study was to determine if specific ketogenic supplements and/or combinations would improve motor performance in rodents with pathology (Wistar Albino Glaxo/Rijswijk, WAG/Rij/WR rats and Glut1 Deficiency Syndrome/G1D mice) and without pathology (Sprague-Dawley/SPD rats) [ 36 , 37 ] and to test whether they are able to offset the postexercise induced blood glucose elevation. WR rat strain is an accepted model of absence epilepsy with comorbidity of low-grade depression, but without pathological changes in locomotor activity/motor performance [ 38 , 39 , 40 ], while G1D mice are models of Glut1 Deficiency Syndrome and show motor dysfunction [ 37 , 41 ]. We hypothesized that nutritional ketosis induced by various ketone therapeutics (KD and exogenous ketone supplements) can improve motor performance in rodent models, as defined by latency to fall from the accelerated rotarod and can offset blood glucose elevation in postexercised states.…”
Section: Introductionmentioning
confidence: 99%